Mitochondrial oxidative stress and dysfunction in arsenic neurotoxicity: A review. Issue 2 (29th October 2015) - Prakash, Chandra; Soni, Manisha; Kumar, Vijay
Abstract: Arsenic is a toxic metalloid present ubiquitously on earth. Since the last decade, it has gained considerable attention due to its severe neurotoxic effects. Arsenic can cross the blood–brain barrier and accumulate in different regions of the brain suggesting its role in neurological diseases. Arsenic exposure has been associated with reactive oxygen species generation, which is supposed to be one of the mechanisms of arsenic‐induced oxidative stress. Mitochondria, being the major source of reactive oxygen species generation may present an important target of arsenic toxicity. It is speculated that the proper functioning of the brain depends largely on efficient mitochondrial functions. Multiple studies have reported evidence of brain mitochondrial impairment after arsenic exposure. In this review, we have evaluated the proposed mechanisms of arsenic‐induced mitochondrial oxidative stress and dysfunction. The understanding of molecular mechanism of mitochondrial dysfunction may be helpful to develop therapeutic strategies against arsenic‐induced neurotoxicity. The ameliorative measures undertaken in arsenic‐induced mitochondrial dysfunction have also been highlighted. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Arsenic is a toxic metalloid present ubiquitously on earth and has gained considerable attention due to its severe neurotoxic effects. Arsenic exposure has been associated with ROS generation which is supposed to be one of its mechanisms for oxidative stress generation. Mitochondria, being the major source of ROS generation may present an important target of arsenic toxicity. The proper functioning of brain depends largely on efficient mitochondrial functions. Multiple studies have reported evidence of brain mitochondrial impairment after arsenic exposure.